The concept of construction of diversion hydropower plants in the Issyk-Kul basin - Turusbekov, Sagyndyk K. (Journal of the Belarusian State University. Ecology, 2018)
The article considers the hydropower potential of small rivers of the Issyk-Kul basin and the concept of its use for energy supply to local consumers, sanatoriums, boarding houses and farms.